2021
DOI: 10.1155/2021/9614953
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Nomogram to Predict Contrast-Induced Acute Kidney Injury in Patients with Congestive Heart Failure Undergoing Coronary Angiography

Abstract: Background. Patients with congestive heart failure (CHF) are vulnerable to contrast-induced kidney injury (CI-AKI), but few prediction models are currently available. Therefore, we aimed to establish a simple nomogram for CI-AKI risk assessment for patients with CHF undergoing coronary angiography. Methods. A total of 1876 consecutive patients with CHF (defined as New York Heart Association functional class II-IV or Killip class II-IV) were enrolled and randomly (2:1) assigned to a development cohort and a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Multinomial multiple logistic regression analyses were performed to examine between the UA and CI-AKI adjusted for age, gender,intra-aortic balloon pump (IABP), congestive heart failure (CHF), anemia, DM, pre-SCr, contrast medium volume, AMI and PCI, which were based on the classic Mehran CIN risk score 4 and relevant literature. 11,12 Furthermore, restricted cubic spline (RCS) was used to investigate the linear tendency of the association between UA value and the risk of CI-AKI. In this method, we selected four SUA values as knots based on UA percentiles, tested the linear and non-linear associations between knots using a cubic function, and presented the smoothly integrated graph.…”
Section: Discussionmentioning
confidence: 99%
“…Multinomial multiple logistic regression analyses were performed to examine between the UA and CI-AKI adjusted for age, gender,intra-aortic balloon pump (IABP), congestive heart failure (CHF), anemia, DM, pre-SCr, contrast medium volume, AMI and PCI, which were based on the classic Mehran CIN risk score 4 and relevant literature. 11,12 Furthermore, restricted cubic spline (RCS) was used to investigate the linear tendency of the association between UA value and the risk of CI-AKI. In this method, we selected four SUA values as knots based on UA percentiles, tested the linear and non-linear associations between knots using a cubic function, and presented the smoothly integrated graph.…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, the baseline characteristics such as age, co-existing conditions, drug combinations, routine blood tests, liver and kidney function, BNP, cardiac enzyme, and D-value were significantly different between patients with and without AKI. Previous studies have revealed consistent predictors of AKI in patients with heart disease, such as age [ 5 , 10 ], IABP [ 7 , 11 , 26 ], diuretic [ 7 , 11 ], white blood cells [ 7 , 10 ], biomarkers of cardiac damage [ 27 ], and hemoglobin [ 5 , 10 , 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological processes underlying contrast-associated AKI are complicated and not yet entirely elucidated. Several risk factors have been identified as contributing to the higher likelihood of AKI, including advanced age, lower baseline creatinine clearance, diabetes mellitus, advanced congestive heart failure, liver disease, pre-existing chronic kidney disease, length of the procedure, large contrast volume, and use of intra-aortic balloon pump (IABP) [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Certain investigations have revealed some biomarkers associated with AKI, such as serum creatinine, cystatin C, neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, and interleukin-18 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation